PENGARUH JUMLAH PENDUDUK DAN PENGANGGURAN TERHADAP JUMLAH RUMAH TANGGA MISKIN (Studi Pada Masyarakat Kecamatan Utan) - Era Prityawati; M Melyana; Binar Dwiyanto Pamungkas (Jurnal Ekonomi & Bisnis, 2022)
This study aims to determine the effect of population and unemployment on the number of poor households in Utan Sub-District. This type of research is associative research. The type of data used is quantitative data obtained from secondary sources related to data on population, unemployment and the number of poor households which are detailed per village in Utan Sub-District in 2021. Data collection is carried out using the documentation method by looking for documents or archives related to the data studied. Data analysis was carried out using multiple linear regression analysis techniques, t and F tests, and the coefficient of determination (R2) test. The results showed that the population and unemployment had a significant effect on the number of poor households in Utan District in 2021, either partially or simultaneously. The degree of influence of the variable population and unemployment on the number of poor households in Utan District in 2021 is 84.5%, while the remaining 15.5% is influenced by other variables not included in the study.